2014
DOI: 10.1152/ajpheart.00872.2013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced p22phoxexpression impairs vascular function through p38 and ERK1/2 MAP kinase-dependent mechanisms in type 2 diabetic mice

Abstract: Type 2 diabetes is associated with vascular complication. We hypothesized that increased nicotinamide adenine dinucleotide phosphate (NADPH) oxidase subunit p22 phox expression impairs vascular endothelium-dependent relaxation (EDR) in type 2 diabetes. Type 2 diabetic (db Ϫ /db Ϫ ) and control (db Ϫ /db ϩ ) mice were treated with reactive oxygen species (ROS) scavenger, polyethylene glycol superoxide dismutase (1,000 U/kg daily ip), or small interfering RNA p22 phox (p22 phox -lentivirus-small interfering RNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…The product of this reaction, peroxynitrite, is in and of itself a powerful oxidant and can exacerbate vascular dysfunction by causing further damage to lipids, proteins and DNA, uncoupling endothelial nitric oxide synthase (eNOS) and diminishing smooth muscle responses to NO [111,112]. In the systemic microvasculature, impaired endothelium-dependent vasodilation and concomitant enhanced Nox-mediated oxidative stress have been observed in microvascular coronary arterioles and mesenteric resistance arteries in a number of cardiovascular diseases, such as obesity [113,114], diabetes [18,19,47,115,116], hypertension [117119] and ischemia-reperfusion [73]. In these studies, elevated expression of Nox subunits is a common characteristic across different cardiovascular pathologies.…”
Section: Systemic Microcirculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The product of this reaction, peroxynitrite, is in and of itself a powerful oxidant and can exacerbate vascular dysfunction by causing further damage to lipids, proteins and DNA, uncoupling endothelial nitric oxide synthase (eNOS) and diminishing smooth muscle responses to NO [111,112]. In the systemic microvasculature, impaired endothelium-dependent vasodilation and concomitant enhanced Nox-mediated oxidative stress have been observed in microvascular coronary arterioles and mesenteric resistance arteries in a number of cardiovascular diseases, such as obesity [113,114], diabetes [18,19,47,115,116], hypertension [117119] and ischemia-reperfusion [73]. In these studies, elevated expression of Nox subunits is a common characteristic across different cardiovascular pathologies.…”
Section: Systemic Microcirculationmentioning
confidence: 99%
“…As a primary source for oxidative stress and reactive oxygen species (ROS) in vascular cells, the contribution of NADPH oxidases (Noxs) to the cardiovascular system in health and disease has been investigated in a plethora of studies [911,1315]. In the microcirculation, Noxs are implicated in a variety of vascular pathologies including arteriolar remodeling [16,17] and endothelial dysfunction [18,19] in systemic microvessels, as well as impaired neurovascular coupling [20] and disrupted blood-brain barrier (BBB) integrity [21] in the cerebral circulation. The current review aims not to be an exhaustive review on the roles of all sources of oxidases in the microcirculation.…”
Section: Introductionmentioning
confidence: 99%
“…These findings further support NADPH oxidase as a functionally relevant source of ROS for regulating coronary vascular tone. As both adenosine and ROS are generated and released under pathophysiological conditions [9,65] and generated ROS mainly exerts a detrimental influence on the coronary vasculature [54][55][56], future studies addressing the role of A 2A AR in ROS-mediated coronary vascular tone regulation in pathophysiological conditions will bring us greater insights into mechanisms underlying ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity might be due to vasoconstrictor ROS vs. vasodilator ROS [29,31] generated from different vascular beds (coronary vs. renal artery) [34,37]. Furthermore, in the coronary vasculature, the varying effects of ROS may depend on which source ROS are generated from (NADPH vs. uncoupled NO synthase) [31,52,53] or the pathophysiological conditions [32,52,53], e.g., diabetes, and the right ventricular hypertrophy [54][55][56]. In accordance with our previous studies [37], the effect of ROS scavenging with EUK134 was comparable with the effect of Nox2 inhibition with gp91 ds-tat in WT isolated hearts (P=0.24), suggesting that the majority of ROS generated by adenosine is likely from Nox2, which leads to increases in coronary flow.…”
Section: Adenosine-induced Increase In Coronary Flow Is Mediated In Pmentioning
confidence: 99%
“…It has been well demonstrated that the increased production of ROS is one of the major causative factors for diabetic angiopathy [24,25]. Mitochondrial electron transport chain, NADPH oxidases (Noxes) and uncoupled nitric oxide synthase are the major sources of hydrogen peroxide (H 2 O 2 ) in vessel walls [26][27][28].…”
Section: Discussionmentioning
confidence: 99%